2018
DOI: 10.1063/1.5064703
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic superconductivity above 10 K in silicon point contacts

Abstract: Silicon, perhaps the most ubiquitously used material in the digital age of today, has also been a material of choice for testing the fundamental differences between various electronic ground states, e.g., metals and insulators. This is mainly because ultimate control has been achieved in growing extremely pure silicon crystals and doping them with varying concentrations of charge carriers and their mobility. Here, we show that by forming mesoscopic point contacts with non-superconducting metals on insulating (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
1
12
2
Order By: Relevance
“…To understand these anomalous features in the PCAR spectra, it becomes pertinent to ask, what is the origin of the large gap of In observed for all contacts with highly doped Si. Can these observations be explained i) simply as experimental artefacts in soft PC spectroscopy or ii) by the fact that highly doped Si might show tip induced superconductivity (TIS) consistent with the recent report by Sirohi et al 33 or iii) on the basis of the Schottky barrier present at the Sm-Sc interface 30 or iv) by the presence of a second superconducting phase appearing at the Sm-Sc interface induced by the proximity effect 9 .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…To understand these anomalous features in the PCAR spectra, it becomes pertinent to ask, what is the origin of the large gap of In observed for all contacts with highly doped Si. Can these observations be explained i) simply as experimental artefacts in soft PC spectroscopy or ii) by the fact that highly doped Si might show tip induced superconductivity (TIS) consistent with the recent report by Sirohi et al 33 or iii) on the basis of the Schottky barrier present at the Sm-Sc interface 30 or iv) by the presence of a second superconducting phase appearing at the Sm-Sc interface induced by the proximity effect 9 .…”
Section: Resultssupporting
confidence: 70%
“…This indicated that the observations for the n++Si-In junction were reflective of a Sm-Sc interface. Furthermore, tip induced superconductivity reported from point contact measurements in highly doped Si with Ag tip 33 was also not observed in the present study.…”
Section: Introductioncontrasting
confidence: 77%
“…The superconducting phase was obtained with a considerable high T c 11 K and superconducting energy gap of 2 meV. 17 shown in figure 4. Subsequently, the superconducting phase under point contacts was examined on both n-doped (As dopants) and p-doped (B-dopants) facets of silicon crystals using various metallic tips exhibiting universal behavior of mesoscopic superconductivity in silicon crystals.…”
Section: Superconductivity Under Point Contacts On Heavily Doped Siliconmentioning
confidence: 95%
“…Recently, evidence of superconductivity was found in moderately doped silicon crystals under point contacts with non-superconducting metallic tips with reasonably high critical temperature(∼ 11K). 17 The superconducting phase was examined in As-doped Si (111) with the mean free path of electrons decide the transport regimes. 48 Ballistic transport regime is said to occur in the condition when the contact diameter becomes smaller than electron's elastic mean free path.…”
Section: Superconductivity Under Point Contacts On Heavily Doped Siliconmentioning
confidence: 99%
See 1 more Smart Citation